NATO IN THE CONTEMPORARY WORLD AND ITS RELATIONS WITH KAZAKHSTAN (ACCORDING TO AN EXPERT OPINION POLL) - ABDRAKHMANOV, Askar; SHAYMERGENOV, Timur (CENTRAL ASIA AND THE CAUCASUS, 2008)
In 2008 the Institute of World Economy and Politics at the First President of the RK Foundation together with the Eurasian Rating Agency circulated a questionnaire in the expert community of Kazakhstan on NATO’s role in the contemporary world and its relations with the RK. The authors have undertaken to summarize the results.The dynamic changes in NATO caused a wide response in the academic, expert, and political community, which was expressed in an avalanche of statements, publications, and studies of real academic value; some of them were obviously suggested by the demands of the times. We all know that since the 1990s the Alliance has been trying to adjust itself to the changing realities and has been actively looking for a new role on the Western and international political scene. Based on the collective defense principle NATO is living through a multisided transformation effort designed to adapt its strategy, tactics, and military-political potential to the changes obvious in the sphere of international security, the scope and intensity of which nobody could predict. Globalization of its strategic activities and stronger position as a factor of the international security architecture that affects the strategic situation in several regions of the world is one of the results of these transformations. NATO is doing a lot to identify and justify the missions found outside the functions outlined in its strategic documents; it is concentrating on the antiterrorist struggle, crisis settlement, and peacekeeping, expansion of its cooperation with the non-members, etc. Its Armed Forces are being modernized and the command and control structure optimized together with the AF’s technical potential; their operational activity has been upgraded to allow NATO to deploy its troops anywhere in the world, etc. The bloc is rapidly acquiring political dimensions and attaching ever greater importance to the diplomatic and non-military aspects of international cooperation.To a certain extent NATO is going global—it is gradually extending by adopting new members and widening the zone of its strategic activity. For the sake of its own security, it is actively “attaching” the so-called young democracies of southeastern Europe (Serbia, Croatia, Bosnia and Herzegovina, Macedonia, and Albania) and the East (Ukraine, probably Belarus and Armenia). Well-known Kazakhstani political scientist Murat Laumulin has pointed out that NATO is working on strategies designed to involve the largest number of states in Western geopolitics. To achieve this aim it is building up its geopolitical presence in all parts of the globe.